JUAL BELI TRANSFUSI DARAH DALAM HUKUM DAN PANDANGAN ISLAM - Hasipa, Hani Siti; Amelia, Lienji; Septiani, Nisya Aulia; Faozi, Akhmad; Supriyadi, Tedi; Nurjanah, Yunisha Husnul (Universitas Mathla’ul Anwar Banten, 2024)
Konsep transfusi darah atau